Analisis Implementasi Dalam Mewujudkan Ekonomi Hijau Di Kalimantan Barat - Inka Muliyani; Agustina Nanda Kartika; Petronila Mely; Tegar Prasetiyo (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
This research aims to examine the application and implementation of a green economy in West Kalimantan by involving collaboration between the West Kalimantan REDD+ Work Program and close communication with indigenous communities as an integral part of these programs. The main focus of this research is fair and sustainable forest management, with the hope that these steps will move West Kalimantan towards a greener future. Even though it is known as a province rich in potential in the agricultural, plantation, forestry, fisheries, mining and mining sectors, West Kalimantan remains committed to the principles of a green economy. For example, the agriculture, forestry and plantation sectors contributed 24% to Gross Regional Domestic Product (GRDP) in 2020. In an effort to increase added value and environmental sustainability, commodity downstreaming and reducing exploitation of natural resources is a strategic focus. The West Kalimantan Provincial Government hopes that all stakeholders can synergize and collaborate to realize the vision of a green economy that not only empowers the community but also protects the environment. This research uses literature study to obtain information and data regarding Implementation Analysis in Realizing a Green Economy in West Kalimantan. Secondary data sources come from journals, news, books, statutory regulations and other documents. To optimize sustainable management of natural resources, the West Kalimantan Provincial Government issued Regional Regulation (Perda) Number 6 of 2018 concerning sustainable management of land-based businesses. The regulation requires land-based entrepreneurs to consider environmental sustainability, eco-efficiency, fairness and benefits to society.  Keywords: Green Economy, Implementation, Natural resources.